The security development lifecycle SDL, a process for developing demonstrably more secure software - Howard, Michael 1965- (Microsoft Press, 2006)
Your customers demand and deserve better security and privacy in their software. This book is the first to detail a rigorous, proven methodology that measurably minimizes security bugs-the Security Development Lifecycle (SDL). In this long-awaited book, security experts Michael Howard and Steve Lipner from the Microsoft Security Engineering Team guide you through each stage of the SDL-from education and design to testing and post-release. You get their first-hand insights, best practices, a practical history of the SDL, and lessons to help you implement the SDL in any development organization. Discover how to: Use a streamlined risk-analysis process to find security design issues before code is committed Apply secure-coding best practices and a proven testing process Conduct a final security review before a product ships Arm customers with prescriptive guidance to configure and deploy your product more securely Establish a plan to respond to new security vulnerabilities Integrate security discipline into agile methods and processes, such as Extreme Programming and Scrum Includes a CD featuring: A six-part security class video conducted by the authors and other Microsoft security experts Sample SDL documents and fuzz testing tool PLUS-Get book updates on the Web. A Note Regarding the CD or DVD The print version of this book ships with a CD or DVD. For those customers purchasing one of the digital formats in which this book is available, we are pleased to offer the CD/DVD content as a free download via O'Reilly Media's Digital Distribution services. To download this content, please visit O'Reilly's web site, search for the title of this book to find its catalog page, and click on the link below the cover image (Examples, Companion Content, or Practice Files). Note that while we provide as much of the media content as we are able via free download, we are sometimes limited by licensing restrictions. Please direct any questions or concerns to booktechoreilly.com.
Title from title screen. - Includes bibliographical references and index. - Print version record
Keywords: Computer software -- Development; Computer security; Computer software -- Reliability; Sécurité informatique; Logiciels; Fiabilité; COMPUTERS; Internet; Security; COMPUTERS; Networking; Security; COMPUTERS; Security; General; Computer software; Development; Computer software; Reliability